Analysis of the core polarization effects in the calculated atomic parameters of Hg iii. Issue 1 (25th January 2020) - de Andrés-García, I; Colón, C
ABSTRACT: The presence of Hg iii in the stellar atmosphere in the stars HgMn χ Lupi and HR7775 was reported by Leckrone et al. and Proffitt et al. In this last work, the authors indicate that the intensities of the spectral lines of 1360.50, 1647.48, and 1738.54 Å of Hg iii are relatively strong compared to the intensities of the spectral lines of Hg ii . Although the explanation given by the authors in their conclusions should be correct, the values of the oscillator strengths used by the authors in some cases were not consistent with the experimental lifetimes obtained by Henderson et al. In addition, some of the lines studied by the authors are widely overlapped with intense lines of Hg iii of the same multiplet. In this paper, we present values of transition probabilities and line broadening by electron collision (Stark effect) of several lines of Hg iii in order to clarify the problems indicated above. Since Hg iii is a heavy element, we include the core polarization effects (using the Cowan's code) in our calculations. Several values of polarizability, taking Fraga values for Hg iv as a starting point, have been considered in this study in order to obtain theoretical values of those parameters close to the experimental ones. The theoretical values of the lifetimes obtained in this study, close to the experimental ones, were obtained for a polarizability value of 3.5 au.